THE INITIATION PLOT IN THE STORIES THE METAMORPHOSIS BY FRANTZ KAFKA AND SAMSA IN LOVE BY HARUKI MURAKAM (Journal of Contemporary Philology, 2023)
Thе paper analyses the stories The Metamorphosis and Samsa in Love through detecting their similarities with the structure of the initiation rites. The analysis uses the findings of anthropology and folklore studies. The paper is divided into two parts. The first part focuses on the story The Metamorphosis. The main ar-gument is that this story by Franz Kafka can be read as a reversed initiation in which the neophyte Gregor Samsa is going backwards till he is no longer part of the community. In the second part of the paper The Metamorphosis is analysed alongside Haruki Murakami’s story Samsa in Love. The two stories can be read as one continuous narrative in which we can see the whole structure of the initi-ation rite. The idea is that the character of Gregor Samsa can be interpreted as a neophyte whose initiation starts in The Metamorphosis and continues in the story Samsa in Love. These two stories function as opposites to one another, but the focus is on the reading which makes the two stories complementary.
Keywords: initiation; Franz Kafka; Haruki Murakami; intertextuality